2015
DOI: 10.3109/00952990.2015.1058390
|View full text |Cite
|
Sign up to set email alerts
|

Review of adjunctive dexmedetomidine in the management of severe acute alcohol withdrawal syndrome

Abstract: The use of dexmedetomidine in the management of severe alcohol withdrawal should be considered as an adjunctive agent. Dexmedetomidine appears to be well tolerated, with an expected decrease in blood pressure and heart rate. Seizures have occurred in patients with alcohol withdrawal despite the use of dexmedetomidine, with and without benzodiazepines, due to lack of γ-aminobutyric acid agonist administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Acute alcoholic hepatitis was defined as an admission aspartate aminotransferase (AST) greater than the upper limit of normal of our laboratory (AST > 37 IU/l). Dexmedetomidine and benzodiazepines were administered according to our hospital’s CIWA protocol (Clinical Institute Withdrawal Assessment for Alcohol Scale) [2, 4, 21, 22]. Survival to hospital discharge was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Acute alcoholic hepatitis was defined as an admission aspartate aminotransferase (AST) greater than the upper limit of normal of our laboratory (AST > 37 IU/l). Dexmedetomidine and benzodiazepines were administered according to our hospital’s CIWA protocol (Clinical Institute Withdrawal Assessment for Alcohol Scale) [2, 4, 21, 22]. Survival to hospital discharge was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Numerous medications in combination or as monotherapy are used for treatment of AW, including α-adrenergic agonists, barbiturates, benzodiazepines (BZDs), β-blockers, butyrophenones, carbamazepine, dexmedetomidine, gabapentin, propofol, and valproic acid. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The primary goals of pharmacologic management of AWS are to minimize symptom severity and prevent major complications. 6,7 The ideal agent should be cross-tolerant with alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…14,37 Adjunctive agents or alternatives to BZDs may reduce these effects. [13][14][15] Phenobarbital (PHB) has been studied for patients across the continuum of AWS over the last 40 years and offers potential advantages to BZDs. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] PHB exerts its effects in as few as 5 minutes with parenteral administration.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown it to be beneficial as an adjuvant medication, specifically reducing the short-term benzodiazepine requirement and providing sedation without causing respiratory depression. [78][79][80] Dexmedetomidine can, however, lead to bradycardia and hypotension. Additionally, given its lack of action at GABA receptors, it does not target the underlying mechanism of alcohol withdrawal and as such, does not treat DTs, alcohol withdrawal seizures, or prevent the progression of AWS.…”
mentioning
confidence: 99%
“…Additionally, given its lack of action at GABA receptors, it does not target the underlying mechanism of alcohol withdrawal and as such, does not treat DTs, alcohol withdrawal seizures, or prevent the progression of AWS. 79 Finally, several small studies have examined the use of baclofen, a pure GABA B agonist. 81,82 However, a recent Cochrane review found that there is insufficient evidence to make a judgement regarding the efficacy and safety of baclofen for AWS; further research will be important to support its use.…”
mentioning
confidence: 99%